Propuesta de una planeación estratégica aplicable a MiPymes de construcción; caso de estudio Ingesec Construcción S.A.S (2023)
Through this work, a Strategic Planning Proposal applicable to construction MSMEs was made; case study Ingesec Construction S.A.S. Currently, the company is a beginner in the construction sector, with low gradual growth, therefore, it does not present a Strategic Planning, which leads to the prompt implementation of procedures and processes for its control, monitoring, evaluation and, if necessary, correction of these. The proposal was developed based on David F's strategic model, which involved developing an EFI, EFE matrix, data that was collected through the interview, which allowed the evaluation and analysis of the company to identify the current situation. of the same generating a SWOT matrix.